Long‐range movement by Hector's dolphins provides potential genetic enhancement for critically endangered Maui's dolphin. Issue 1 (7th March 2013) - Hamner, Rebecca M.; Constantine, Rochelle; Oremus, Marc; Stanley, Martin; Brown, Phillip; Scott Baker, C.
Abstract For endangered populations with low genetic diversity, low levels of immigration could lead to genetic rescue, reducing the risk of inbreeding depression and enhancing chances of long‐term species survival. Our genetic monitoring of Maui's dolphins revealed the first contemporary dispersal of their sister subspecies, Hector's dolphin, from New Zealand's South Island into the Maui's dolphin distribution along ~300 km of the North Island's northwest coast. From 2010 to 2012, 44 individuals were sampled within the Maui's dolphin distribution, four of which were genetically identified as Hector's dolphins (two living females, one dead female, one dead male). We also report two Hector's dolphins (one dead female neonate, one living male) sampled along the North Island's southwest coast, outside the presumed range of either subspecies. Together, these records demonstrate long‐distance dispersal by Hector's dolphins (≥400 km) and the possibility of an unsampled Hector's dolphin population along the southwest coast of the North Island. Although two living Hector's dolphins were found in association with Maui's dolphins, there is currently no evidence of interbreeding between the subspecies. These results highlight the value of genetic monitoring for subspecies lacking distinctive physical appearances as such discoveries are not detected by other means, but have important conservation implications.